Concept for a hyperspectral remote sensing algorithm for floating marine macro plastics. (January 2018) - Goddijn-Murphy, Lonneke; Peters, Steef; van Sebille, Erik; James, Neil A.; Gibb, Stuart
Abstract: There is growing global concern over the chemical, biological and ecological impact of plastics in the ocean. Remote sensing has the potential to provide long-term, global monitoring but for marine plastics it is still in its early stages. Some progress has been made in hyperspectral remote sensing of marine macroplastics in the visible (VIS) to short wave infrared (SWIR) spectrum. We present a reflectance model of sunlight interacting with a sea surface littered with macro plastics, based on geometrical optics and the spectral signatures of plastic and seawater. This is a first step towards the development of a remote sensing algorithm for marine plastic using light reflectance measurements in air. Our model takes the colour, transparency, reflectivity and shape of plastic litter into account. This concept model can aid the design of laboratory, field and Earth observation measurements in the VIS-SWIR spectrum and explain the results. Highlights: A concept spectral model is derived for the calculation of sea surface plastic. Marine plastic litter should be visible with spectral light reflectance measurements. Light reflectance controls the remote sensing signal of marine plastic litter.